Symptomatic COVID-19 re-infection in a child, three months after primary infection - Varghese, Serena M.; M., Mubeena (International Journal of Contemporary Pediatrics, 2020)
The natural course of Coronavirus disease 2019 (COVID-19) is still not fully known. Re-infection with Severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) in recovered children has not been reported till date. We describe a case of symptomatic COVID-19 re-infection in a child after an asymptomatic period of three months following an international travel. The child had RT-PCR positivity and systemic inflammation, but did not have multi organ dysfunction as in pediatric inflammatory multisystem syndrome.